Filsafat Ilmu Ekonomi Syariah Sebagai Landasan Sistem Ekonomi Syariah Bagi Pendidikan Umat Islam - Adelia Safitri; Maulida Rahma; Safnah Soleha; Ahmad Wahyudi Zein (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The philosophy of Islamic economics is an important foundation in building an economic system based on Islamic values. Based on the Qur'an, Hadith, ijma, and qiyas, this philosophy offers a holistic conceptual framework to answer modern economic challenges. This research aims to describe the principles, characteristics, and main objectives of Islamic economics based on the values of tawhid, justice, and benefit. The method used in this research is descriptive qualitative based on literature study to explore the relationship between the philosophy of science, sharia principles, and the application of Islamic economics in the Islamic finance and banking sector. The results show that Islamic economics not only offers practical solutions to various economic problems, but also instills moral and spiritual values to create prosperity in the world and the hereafter. The development of Islamic economics in Indonesia is influenced by internal factors such as the large Muslim population and external factors such as the influence of the global Islamic banking system.